Pathological α-synuclein elicits granulovacuolar degeneration independent of tau - Dylan J. Dues; Madalynn L. Erb; Alysa Kasen; Naman Vatsa; Erin T. Williams; An Phu Tran Nguyen; Michael X. Henderson; Darren J. Moore (Translational Neurodegeneration)
Abstract Background Pathologic heterogeneity is a hallmark of Lewy body dementia (LBD), yet the impact of Lewy pathology on co-pathologies is poorly understood. Lewy pathology, containing α-synuclein, is often associated with regional tau pathology burden in LBD. Similarly, granulovacuolar degeneration bodies (GVBs) have been associated with tau pathology in Alzheimer’s disease. Interestingly, GVBs have been detected in a broad range of neurodegenerative conditions including both α-synucleinopathies and tauopathies. Despite the frequent co-occurrence, little is known about the relationship between α-synuclein, tau, and granulovacuolar degeneration. Methods We developed a mouse model of limbic-predominant α-synucleinopathy by stereotactic injection of mouse α-synuclein pre-formed fibrils (PFFs) into the basal forebrain. This model was used to investigate the relationship of α-synuclein pathology with tau and GVB formation. Results Our model displayed widespread α-synuclein pathology with a limbic-predominant distribution. Aberrantly phosphorylated tau accumulated in a subset of α-synuclein inclusion-bearing neurons, often colocalized with lysosomes. Many of these same neurons also contained CHMP2b- and CK1δ-positive granules, established markers of GVBs, which suggests a link between tau accumulation and GVB formation. Despite this observation, GVBs were also detected in tau-deficient mice following PFF injection, suggesting that pathological α-synuclein alone is sufficient to elicit GVB formation. Conclusions Our findings support that α-synuclein pathology can independently elicit granulovacuolar degeneration. The frequent co-accumulation of tau and GVBs suggests a parallel mechanism of cellular dysfunction. The ability of α-synuclein pathology to drive GVB formation in the absence of tau highlights the broader relevance of this process to neurodegeneration with relevance to the pathobiology of LBD.